A Methodological Blueprint for Social Sciences Research – The Social Sciences Research Methodology Framework - Norbert E Haydam; Pieter Steenkamp (EIRP Proceedings, 2020)
Most research practice constructs in social sciences are predominantly well defined and constructed, yet many authors hold different interpretations of certain key terms and concepts, causing a degree of confusion, overlap and uncertainty. The term ‘qualitative research’ is such a case in point. Not only does this concept show different interpretations by many authors, but there is also uncertainty about how this concept relates to exploratory research or other contemporary social research practice concepts. It is also unclear whether a longitudinal research approach can be applied to qualitative research or related concepts. In order to provide a clear perspective on the above-mentioned dilemma, the authors recommend the application of the socalled social sciences research methodology framework, which follows Saunders’ (2009) research ‘onion’ approach. This proposed framework provides an uncluttered and unambiguous guide to social sciences research methodology with relevant social sciences methodologies and constructs clearly positioned in a structured and simplistic way. The research employed was fundamental in nature. Inductive rational philosophical reasoning was used, and a theoretical analysis was applied through a systematic literature review of published text. In the end, the framework provides a unified understanding of most social sciences research constructs and at the same time acts as an aiding tool in the evaluation of all academic work, thereby enabling various examiners to provide clear and unambiguous guidance to contributors and students alike.